PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVA SD NEGERI 31 PEKANBARU - Dewi, Suhaiti; ', Syahrilfuddin; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning science study class IVc SD Negeri 169 Pekanbaru. KKM achieved by school was 75. From 36 students who achieve KKM just 20 students (55,56%) while students who didâ€™nt achieve KKM is 16 students (44.44%) with a class average of 72,22. The purpose of this research to improve learning outcomes IPS class IVA SD Negeri 31 Pekanbaru with the application of learning models Quantum Teaching. The results obtained by the average value of 72,22 basic score increased in the first cycle of 6,66% to 78,88. In the second cycle the average value of students also increased by 11,89% to 84,11. On the basic of classical completeness score IPS student learning outcomes is only 55,56% (not finished). After the professor of applied learning model Quantum Teaching in the first cycle classical completeness increased to 75% (finished), and the second cycle of classical completeness obtained are increased to increase to 91,66%. Activities of teachers at the first meeting of first cycle acquire a percentage of 70,45% with enough categories. The second meeting increased to 77,27% in good categories. In the first meeting of second cycle increased to 88,63% with good category. At the second meeting increased to 97,72% with very good category. Activities of students in the first meeting of the first cycle acquire a percentage of 56,81% with enough categories. The second meeting increased to 75% in good categories. In the first meeting of the second cycle increased to 88,63% with good category. At the second meeting increased to 95,45% with good category.Â Key Words : Quantum Teaching, learning outcomes IPS